Can acute care surgeons perform while fatigued? An EAST multicenter study. Issue 3 (September 2018) - Schuster, Kevin M.; Hazelton, Joshua P.; Rattigan, Deviney; Nguyen, Linh; Kim, Dennis; Spence, Lara H.; Turay, David; Luo-Owen, Xian; Perez, Javier Martin; Dayal, Saraswati; Blatt, Melissa; Hill, Casey; et al.
Abstract : BACKGROUND: Fatigued surgeon performance has only been assessed in simulated sessions or retrospectively after a night on call. We hypothesized that objectively assessed fatigue of acute care surgeons affects patient outcome. METHODS: Five acute care surgery services prospectively identified emergency cases over 27 months. Emergency cases were defined by the surgeon identifying the patient as requiring immediate operation upon consultation or admission. Within 48 hours, surgeons reported sleep time accumulated before operation, if nonclinical delays to operation occurred, and patient volume during the shift. To maximize differences, fatigued surgeons were defined as performing a case after midnight without having slept in the prior 18 hours. Rested surgeons performed cases at or before 8 PM or after at least 3 hours of sleep before operation. A four-level ordinal scale was used to assign case complexity. Hierarchical logistic regression models were constructed to assess the impact of fatigue on mortality and major morbidity while controlling for center and patient level factors. RESULTS: Of 882 cases collected, 611 met criteria for fatigue or rested. Of these cases, 370 were performed at night and 182 by a fatigued surgeon. Rested surgeons were more likely to be operating on an older or female patient; other characteristics were similar. Mortality and major morbidity were similar between fatigued and rested surgeons (12.1% vs 12.1% and 46.9% vs 48.9%), respectively. After controlling for center and patient factors, surgeon fatigue did not affect mortality or major morbidity. Mortality variance was 6.30% and morbidity variance was 7.02% among centers. CONCLUSION: Acute care surgeons have similar outcomes in a fatigued or rested state. Work schedules for acute care surgeons should not be adjusted to shifts less than 24 hours for the sole purpose of improving patient outcomes. LEVEL OF EVIDENCE: Prognostic study, level IV. Abstract : Supplemental digital content is available in the text.